2020
DOI: 10.1002/cam4.3520
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of C‐reactive protein in patients with head and neck squamous cell carcinoma: A meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Some routinely measured laboratory analyte baselines have been shown to have prognostic importance in malignant diseases. Both prospective and retrospective studies and also meta-analyses have described the poor prognostic role of elevated baseline C-reactive protein (CRP) (1)(2)(3)(4), crosslinked fibrin degradation products (D-dimer) (5)(6)(7)(8), lactate dehydrogenase (LDH) (9)(10)(11)(12), and decreased albumin (13)(14)(15) in cancer. Deme and Telekes have also reviewed the value of elevated CRP (16), D-dimer (17), LDH (18), and decreased albumin (19) for poor outcomes of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some routinely measured laboratory analyte baselines have been shown to have prognostic importance in malignant diseases. Both prospective and retrospective studies and also meta-analyses have described the poor prognostic role of elevated baseline C-reactive protein (CRP) (1)(2)(3)(4), crosslinked fibrin degradation products (D-dimer) (5)(6)(7)(8), lactate dehydrogenase (LDH) (9)(10)(11)(12), and decreased albumin (13)(14)(15) in cancer. Deme and Telekes have also reviewed the value of elevated CRP (16), D-dimer (17), LDH (18), and decreased albumin (19) for poor outcomes of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…CRP, an acute-phase inflammatory protein, is synthesized in the liver in response to inflammation. Many studies have demonstrated that CRP was associated with cancer survival (36,(40)(41)(42)(43)(44)(45). In addition, the production of CRP in the liver is stimulated by IL-6 (46).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the discrepancies in the results of the studies outlined ( Supplementary Table 1 ) above, Chen et al conducted a meta-analysis and reported that an elevated pretreatment CRP level is an indicator of poor prognosis in HNSCC ( 36 ). To date, no Chinese studies have investigated the effects of serum CRP level on the prognosis of patients with HNSCC, including cancers of the hypopharynx, nasopharynx, larynx, and oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that CRP acts as the dominant ligand for the LOX-1 receptor. There is evidence that CRP is suggested as a ligand for LOX-1 and induced genes involved in tumorigenesis [33,34]. In addition to the ligands for LOX-1 and CD-36, direct bacterial interaction with these receptors may have caused the molecular changes observed in gastric cells.…”
Section: Discussionmentioning
confidence: 99%